Integração regional e participação social: um estudo sobre as reuniões especializadas do MERCOSUL - Firmino , Matheus Pereira (2018)
The present research is dedicated to the study of social participation in MERCOSUL institutional framework. First configured only to be a regional block of strictly market order, MERCOSUL pass through a process of changing in political and ideological terms from the election of progressive governments in South America. The social base of these governments is largely composed by Social Movements and Trade Union Organizations that were present in diverse experiences of direct democracy and citizen participation and articulated a series of networks and forums throughout the region. In MERCOSUL it wasn't different, several movements and organizations tried to focus on the block's paths and demand institutional spaces that gave a formal character to their representation and where they could construct regional policies for each segment considering its particular characteristics. However, there are considerable variation in institutional strength in the space. Therefore, we will analyze how the characteristics of Family Farmers and Youth Movements, that are present in what are known as Specialized Meetings of MERCOSUL, reflects in their institutional strengthening.